Enantioselective Construction of Quaternary Stereogenic Carbon Atoms by the Lewis Base Catalyzed Additions of Silyl Ketene Imines to Aldehydes. Issue 30 (7th July 2014) - Denmark, Scott E.; Wilson, Tyler W.; Burk, Matthew T.
Abstract Silyl ketene imines derived from a variety of α‐branched nitriles have been developed as highly useful reagents for the construction of quaternary stereogenic centers via the aldol addition reaction. In the presence of SiCl4 and the catalytic action of a chiral phosphoramide, silyl ketene imines undergo extremely rapid and high yielding addition to a wide variety of aromatic aldehydes with excellent diastereo‐ and enantioselectivity. Of particular note are the high yields and selectivities obtained from electron‐rich, electron‐poor, and hindered aldehydes. Linear aliphatic aldehydes did react with good diastereo‐ and enantioselectivity in the presence of nBu4N+I−, but branched aldehydes were much less reactive. Semiempirical calculations provided a rationalization of the observed diastereo‐ and enantioselectivity via open transitions states.